DEFINITION OF SPECIFIC WHEEL AND RAIL PROFILES (Perner's Contacts, 2017)
In modeling the dynamics of a rail vehicle ride, one of the important input parameters is the profile geometry of the wheel and rail treads. Commonly available simulation programs have databases containing some standardized profiles, or allow the profile to be added to the database. However, complications arise when a specific profile is required in the simulation analysis. Its geometry must be entered in the required form necessary to ensure compatibility with the structure of the inputs of the computational software, that is, in the form of coordinates of the knot points that can be used to render the curve and thus define the desired profile. Simulation programs, however, do not have the ability to efficiently generate these coordinates. Since this is a lengthy process, the author team has created a program to define profiles based on their common drawing documentation.
Keywords: knot points coordinate calculation; specific wheel and rail tread geometry calculation of points; variable rail profile